Low prevalence of behavioural and emotional problems among Swiss paediatric patients with inflammatory bowel disease. Issue 1 (19th October 2012) - Herzog, Denise; Landolt, Markus A; Buehr, Patrick; Heyland, Klaas; Rogler, Daniela; Koller, Rebekka; Rueger, Vanessa; Pittet, Valérie; Nydegger, Andreas; Spalinger, Johannes; Schäppi, Michela; Schibli, Susanne; et al.
Abstract : Objectives: Whether behavioural and emotional maladjustment is more prevalent in children with inflammatory bowel disease (IBD) than in healthy controls remains controversial. The aim of this study was to assess paediatric IBD patients for problems with emotional and behavioural adjustment and to examine associations with clinical and demographic variables. Methods: Data from paediatric patients with IBD enrolled in the Swiss IBD Cohort Study and the results of both the parent-rated Strengths and Difficulties Questionnaire (SDQ) and the self-reported Child Depression Inventory (CDI) were analysed. Of the 148 registered patients, 126 had at least one questionnaire completed and were included. Results: The mean age of 71 patients with Crohn's disease (44 males, 27 females) was 13.4 years, and 12.8 years for the 55 patients with ulcerative or indeterminate colitis. The mean duration of disease was 1.2 and 2.7 years, respectively. The total score of the SDQ was abnormal in 11.4% of cases compared to 10% in the normal population. Abnormal sub-scores were found in 20.2% of subjects for the domain of emotional problems and in 17.1% for problems with peers. The total CDI T score indicated a significantly lower prevalence of clinical depression in IBD patients than in normal youth. No correlation between the total SDQ scores or the CDI T scores and gender, type or duration of IBD, inflammatory markers or disease scores was found. Conclusions: The prevalence of problems with behavioural and emotional adjustment among Swiss paediatric IBD patients is low and comparable to that of the normal population.